Evaluating the Impact of Diverse Writing Practices on EFL Learners’ Proficiency and Writing Anxiety - Sitepu, Setiana Sri Wahyuni (IJLHE: International Journal of Language, Humanities, and Education, 2025)
This study examines how varied writing practices influence the writing performance and emotional responses of English as a Foreign Language (EFL) learners. Given that writing is widely regarded as one of the most demanding language skills, particularly in foreign language contexts, the research focuses on the integration of project-based learning, dialogue journals, automated writing evaluation (AWE), and self-regulated learning (SRL). The aim is to assess their effects on key aspects of writing: grammar, vocabulary, content, coherence, text length, and writing anxiety. Employing an explanatory sequential mixed methods design, the study involved 20 B2-level EFL students, equally assigned to experimental and control groups. Over an eight-week period, both groups completed structured weekly writing tasks, but the experimental group received supplementary instruction incorporating the four targeted writing strategies. A holistic scoring rubric was used to assess writing performance, and focus group interviews were conducted to capture learners’ perceptions. Quantitative analysis revealed that the experimental group demonstrated statistically significant improvement in grammar and vocabulary, with no notable gender differences. Thematic analysis of the qualitative data yielded two main themes: (1) challenges in the writing process, such as idea generation and coherence, and (2) increased motivation and heightened grammar awareness. Students reported that despite initial difficulties—especially related to translation and coherence—the implemented practices enhanced their motivation and confidence. These findings highlight the pedagogical value of integrating structured, varied writing activities into EFL instruction. The study concludes by recommending broader adoption of such practices to promote both linguistic competence and affective growth in language learners.